Naloxone reversal of the cardiorespiratory depressant effects of opioids and mixtures of opioids and stimulants in rats - Vazquez, Jacqueline M.; Seaman, Robert W.; Caldron, Drew; Collins, Gregory T. (Frontiers in Pharmacology, 2025)
Co-use of opioids (e.g., fentanyl) and stimulants (e.g., methamphetamine; METH) contributed to >30% of the almost 106,000 fatal overdoses in the United States in 2023. Although NarCan® (naloxone) is effective at reversing opioid-induced cardiorespiratory depression, larger and/or more frequent doses are often required for fentanyl and multi-drug overdoses involving fentanyl. Using collar-based pulse oximetry, this study characterized the effects of intravenous (IV) fentanyl (0.0056–0.56 mg/kg), heroin (0.32–5.6 mg/kg), and METH (0.1–1 mg/kg), as well as mixtures of 0.56 mg/kg fentanyl +1 mg/kg METH and 5.6 mg/kg heroin +1 mg/kg METH on blood oxygen saturation (SpO2), heart rate (HR), and breath rate (BR) in male and female Sprague-Dawley rats. To evaluate the potency and effectiveness of naloxone to reverse cardiorespiratory depression, naloxone (0.01–3.2 mg/kg; IV) or vehicle was administered 5 min after opioids or opioid + stimulant mixtures. Naloxone was fully effective at reversing the effects of fentanyl and heroin alone but was more potent for fentanyl. Naloxone was fully effective and equipotent at reversing the cardiorespiratory effects of heroin and heroin + METH but was less potent and less effective at reversing the cardiorespiratory effects of fentanyl + METH compared to fentanyl alone. When administered after fentanyl, heroin, or heroin + METH, naloxone recovered baseline SpO2 in all rats, however, SpO2 was only recovered in 75% of rats treated with fentanyl + METH. These findings suggest that naloxone may be less potent and effective at reversing fentanyl-induced cardiorespiratory depression when METH is co-administered.